Drug-resistant tuberculosis in the WHO Western Pacific Region - Tauhid Islam; Tom Hiatt; Cornelia Hennig; Nobuyuki Nishikiori (World Health Organization Regional Office for the Western Pacific, 2014)
Objective: To review the latest information about tuberculosis (TB) drug resistance and programmatic management of drug-resistant TB in the Western Pacific Region of the World Health Organization (WHO). Methods: We analysed routine data reported by countries to WHO from 2007 to 2013, focusing on data from the following: surveillance and surveys of drug resistance, management of drug-resistant TB and financing related to multidrug-resistant TB (MDR-TB) management. Results: In the Western Pacific Region, 4% (95% confidence interval [CI]: 3-6) of new and 22% (95% CI: 18-26) of previously treated TB cases were estimated to have MDR-TB; this means that in 2013, there were an estimated 71 000 (95% CI: 47 000-94 000) MDR-TB cases among notified pulmonary TB cases in this Region. The coverage of drug susceptibility testing (DST) among new and previously treated TB cases was 3% and 20%, respectively. In 2013, 11 153 cases were notified-16% of the estimated MDR-TB cases. Among the notified cases, 6926 or 62% were enrolled in treatment. Among all enrolled MDR-TB cases, 34% had second-line DST and of these, 13% were resistant to fluoroquinolones (FQ) and/or second-line injectable agents. The 2011 cohort of MDR-TB showed a 52% treatment success. Over the last five years, case notification and enrolment have increased more than five times, but the gap between notification and enrolment widened. Discussion: The increasing trend in detection and enrolment of MDR-TB cases demonstrates readiness to scale up programmatic management of drug-resistant TB at the country level. However, considerable challenges remain.